Analisis Penerapan Metode Pembelajaran Diskusi Kelompok Terhadap Pemahaman Siswa Pada Pembelajaran di SMA Negeri 21 Medan - Simeon Adrian Simatupang; Elsadai Ria Veronika Situmorang; Irma Chintia Simbolon; Andi Taufiq Umar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This type of research is qualitative with a case study which aims to analyze the application of the group discussion learning method to students' understanding of integrated social studies learning material at SMA Negeri 21 Medan. The group discussion method was applied as an effort to increase students' understanding of complex integrated social studies material. The respondents in this study were class X5 and in research. This research uses primary data obtained through interviews with 10 students and 45 students XI IPS 3 direct observation of students at SMA Negeri 21 Medan who are the samples or respondents to this research. The results of the research show that the application of the group discussion learning method significantly increases students' understanding of integrated social studies learning material. Students who were involved in group discussions showed increased ability to understand integrated social studies concepts and were able to relate information between integrated subjects. The application of the group discussion learning method is effective in increasing students' understanding of integrated social studies learning material at SMA Negeri 21 Medan.